Investigation of Pd/TiO2/Si MIS capacitor as hydrogen sensor - Shubham K.; Khan R.U.; Chakrabarti P. (My University, 2025)
Purpose - This paper aims to investigate the gas-sensing capability of Pd/TiO2/Si MIS capacitor using capacitance versus gate voltage (C-V ) response as a function of hydrogen gas concentration varying from 0.1 to 2 ppm at 300 kHz frequency. Design/methodology/approach - The objective is to fabricate a metal-insulator-semiconductor (MIS) capacitor sensor based on TiO2-thin-film insulator deposited by sol-gel spin-coating process. Gas-sensing signal derived on exposure to hydrogen with concentration varying from 0.1 to 2 ppm at different operating temperatures (room temperature to 1,500°C) was measured as variation in flat-band voltage in C-V characteristics of the MIS capacitor. Findings - High sensitivity of the sensor is attributed to the large change of interface state charges because of the large surface-to-volume ratio of the nano-structured TiO2. The values of response time as well as the recovery time have also been estimated and are found to be comparable to that observed in the case of conventional Metal Oxide Semiconductor (MOS) structure. Research limitations/implications - The use of Si substrate restricts the performance of gas sensors to 200°C, as the Si substrate begins to show conductive nature. Originality/value - This paper deals with an MIS capacitor gas sensor which replaces conventional insulating material by TiO2 and uses a high-quality fabrication procedure for controlled growth of novel surface structure. © Emerald Group Publishing Limited.